Hammer acceleration due to thrower and hammer movement patterns - Murofushi, K.; Sakurai, S.; Umegaki, K.; Takamatsu, J. (Sports Biomechanics, 2007)
Ground reaction force and wire tensile force were measured during test throws by three hammer throwers: the Asian record holder, who had a personal best of 83.47 m at the time of the investigation, and two university athletes, with personal bests of 59.95 m and 46.30 m respectively. They were filmed using three high-speed video cameras (250 Hz). The displacements of the hammer head and the athletes' centres of mass were calculated using three-dimensional analysis procedures. The Asian record holder's centre of mass and the hammer head on the final two turns exhibited approximate conjunctions of the hammer high point and the thrower's low point and vice versa about the hammer's azimuth angle. It is conjectured that the reason why the thrower's movement is asynchronous with the hammer's movement by approximately half a turn is to accelerate the hammer head in a manner similar to the way that the amplitude of a pendulum increases when it is pulled upward by a string against the downward movement of the swinging weight.